HALAL TOURISM AND SERVICE EXCELLENCE: KEY DRIVERS OF TOURIST SATISFACTION IN TANJUNG PINANG - Tasriani, Tasriani; Eravia, Diana; Zuhra, Fatimah (Jurnal Al-Iqtishad, 2024)
This study aims to analyze the influence of halal tourism attraction and service quality on tourist satisfaction in Tanjung Pinang City. The research uses a quantitative method with a survey approach. Data was collected through a questionnaire distributed to tourists visiting Tanjung Pinang. Multiple linear regression analysis was used to test the relationship between Halal Tourism Variables and Service Quality on Tourist Satisfaction. The influence of the halal tourism variable by 20% affects tourist satisfaction, while the quality of service affects the tourist satisfaction variable by 46%. The hypothesis test shows that halal tourism variables and service quality have a significant effect on tourist satisfaction with the result of a determination coefficient of 76.9%. This shows a considerable influence of halal tourism variables and service quality so that facilities and services in accordance with Islamic principles are very important in attracting and retaining tourists. Therefore, tourist destination managers and stakeholders in Tanjung Pinang need to focus on developing halal facilities and improving service quality to attract more tourists and ensure they have a satisfying experience.